Firefly Garden Sebagai Pusat Penelitian, Pendidikan dan Pariwisata di Kabupaten Klaten - Ismail, Noor Kholid, Ir. Nurhasan, MT, Ir. Samsudin Raidi, MSc (2015)
Firefly is a type of insect that can emit a yellow or green light from its body. The existence of fireflies in nature has an important role for the sustainability of the balance of biological and technological advances in the health field. Firefly populations are reducing in number. Some time ago fireflies are easy to find, especially in the villages, but now they are very rarely to be seen. The possibility of its presence has been threatened due to the opening of land and forests. As a result of this situation, many of us only know and have little information of fireflies. Manjung village, Ngawen District of Klaten district, is one of the places where there are habitats and populations of wild fireflies that live in rice fields. From the point of view where the problems occurred, to protect the population of fireflies in Klaten district, concept of Firefly Garden area could be the solution for the survival of fireflies where in the region, there is a cultivation of fireflies, a place to study and travel to see the beauty of light emitted by fireflies. To add the educational value in Firefly Garden area, there is a museum with various types of insects that can be learned by any visitor of Firefly Garden area. From the discussion above, it can be concluded that the firefly is one of the insects of which existence is endangered, and a place is needed to nurture and preserve the viability of fireflies, taking advantage of technologies developments in the form of facilities and support so that fireflies are cultured and can be studied and utilized for the benefit of human life.